The TSPO-specific Ligand PK11195 Protects Against LPS-Induced Cognitive Dysfunction by Inhibiting Cellular Autophagy - Lan, Nannan; Liu, Yongxin; Juan, Zhaodong; Zhang, Rui; Ma, Baoyu; Xie, Keliang; Sun, Lina; Feng, Hao; Sun, Meng; Liu, Jianfeng (Frontiers in Pharmacology, 2021)
Perioperative neurocognitive disorders (PND) is a common postoperative neurological complication. Neuroinflammation is a major cause that leads to PND. Autophagy, an intracellular process of lysosomal degradation, plays an important role in the development and maintenance of nervous system. PK11195 is a classic translocator protein (TSPO) ligand, which can improve the cognitive function of rats. In this study, we evaluate the protective effect of PK11195 on the learning and memory of rats. A rat model of lipopolysaccharide (LPS)-induced cognitive dysfunction (PND) was established by intraperitoneal injection of LPS. Morris Water Maze (MWM), Western blot, qRT-PCR, confocal microscopy and transmission electron microscopy (TEM) were used to study the role of TSPO-specific ligand PK11195 in LPS-activated mitochondrial autophagy in rat hippocampus. We found that PK11195 ameliorated LPS-induced learning and memory impairment, as indicated by decreased swimming distances, escape latencies and increased target quadrant platform crossing times and swimming times during MWM tests. TSPO, ATG7, ATG5, LC3B and p62 protein and mRNA expression increased in rat hippocampus in the PND model rats. The PND model rats also had severe cell damage, the nuclear membrane is blurred, mitochondrial vacuolation is severe, and a large number of autophagosomes and phagocytic vesicles are visible. PK11195 pretreatment significantly decreased the expression of TSPO, ATG7, ATG5, LC3B and p62 protein and mRNA, as well as mitochondrial damage. These findings suggested that PK11195 may alleviate the damage of LPS-induced cognitive dysfunction of rats by inhibiting microglia activation and autophagy.